Level of Exercise Awareness Among Students of An-Nur Buntet Islamic Boarding School, Cirebon - Maulana, M.Iqbal; Suganda, Mikkey Anggara; Adiman, Adiman; Widyastuti, Suciati Rahayu; Farihin, Farihin (Jurnal Jembatan Efektivitas Ilmu dan Akhlak Ahlussunah Wal Jama’ah, 2026)
Study purpose. Awareness of exercise is an important aspect in efforts to maintain physical and mental health, especially for teenagers who are in boarding educational environments such as Islamic boarding schools. This research aims to describe the level of sports awareness of students at the An-Nur Buntet Cirebon Islamic Boarding School, which includes aspects of knowledge, attitudes towards sports activities, as well as analyzing differences in the level of knowledge between male and female students. Materials and methods. This research uses a quantitative approach with descriptive methods. The sampling technique used total sampling with a total of 40 students as respondents. Data collection was carried out through a questionnaire consisting of 17 questions. Data analysis was carried out using descriptive statistics, determining categories based on mean and standard deviation values, the Shapiro–Wilk normality test, Levene’s Test of homogeneity, and testing differences using the independent sample t-test. Results. The research results show that the level of knowledge, attitudes, participation and support of Islamic boarding schools for students’ exercise awareness is in the medium category. Apart from that, the results of the hypothesis test showed that there was no significant difference between the level of knowledge of male students and female students regarding exercise awareness (sig. 0.129 > 0.05). Conclusion. This research provides a contribution in the form of empirical information regarding the level of sports awareness among students and can be a basis for developing more targeted and sustainable sports programs in the Islamic boarding school environment.